2010
DOI: 10.4028/www.scientific.net/ssp.159.57
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Nanosized Barium Hexaferrite Powders Obtained by Microemulsion Technique

Abstract: Abstract. Thin hexagonal barium hexaferrite particles synthesized using the microemulsion technique were studied. A water-in-oil reverse microemulsion system with cetyltrimethylammonium bromide (CTAB) as a cationic surfactant, n-butanol as a co-surfactant, n-hexanol as a continuous oil phase, and an aqueous phase were used. The microstructural and magnetic properties were investigated. The particles obtained were mono-domain with average particle size 280 nm. The magnetic properties of the powder were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…(10a) the grain morphology appear totally plate -like shape which is clearly indicated the formation of barium ferrite. Barium hexaferrite nanoparticles with plate-like morphology is the best for the electromagnetic wave absorption application [9]. Also for the composite layer SEM images show the grain microstructure as a combination of spherical and plate like structure which is an evidence for the gradation in FGMs samples and resulting in properties variation.…”
Section: Fe-scanning Electron Microscopy (Fesem) Analysismentioning
confidence: 92%
“…(10a) the grain morphology appear totally plate -like shape which is clearly indicated the formation of barium ferrite. Barium hexaferrite nanoparticles with plate-like morphology is the best for the electromagnetic wave absorption application [9]. Also for the composite layer SEM images show the grain microstructure as a combination of spherical and plate like structure which is an evidence for the gradation in FGMs samples and resulting in properties variation.…”
Section: Fe-scanning Electron Microscopy (Fesem) Analysismentioning
confidence: 92%
“…Water-in-oil microemulsions have also been applied to prepare single domain M-type hexaferrite particles. Koutzarova and coworkers used a reverse microemulsion containing cetyltrimethylammonium bromide as cationic surfactant, n-butanol as co-surfactant, n-hexanol as a continuous oil phase, and water to obtain, after a calcination step at 900 • C, pure Baferrite nanoparticles with average size 280 nm [103]. Most of the particles were found to have an almost perfect hexagonal shape with average aspect ratio diagonal/thickness of 7.7, although the smallest ones (ca.…”
Section: Experimental Methods To Prepare Nanosized Hexagonal Ferrite ...mentioning
confidence: 99%
“…It is suggested that a combination of dopants can be used to control or to reduce the coercivities with only a small change of their saturation magnetizations. Thus, the substitutions of Fe ions by isovalent cations can be generally investigated BaM constituent element iron can be replaced by other metal cations from the group of transition which has almost the same size as Co, Zn, Ni and Mn [5]. This study concentrates synthesis of barium hexaferrite by doping Mn with the variable value x = 0; 0.2; 0.4; and 0.6 and calcinations at 400, 600, and 800 0 C. Furthermore characterization of barium hexaferrite powder with doping to determine the changes that occur after being given additional element Mn dopants and calcinations temperature.…”
Section: Introductionmentioning
confidence: 99%